A comprehensive review of planning, modeling, optimization, and control of distributed energy systems - Hao, Junhong; Yang, Yongping; Xu, Chao; Du, Xiaoze (Carbon Neutrality (Online), 2022)
Distributed energy system, a decentralized low-carbon energy system arranged at the customer side, is characterized by multi-energy complementarity, multi-energy flow synergy, multi-process coupling, and multi-temporal scales (n-M characteristics). This review provides a systematic and comprehensive summary and presents the current research on distributed energy systems in three dimensions: system planning and evaluation, modeling and optimization, and operation and control. Under the regional environmental, resource, and policy constraints, planning distributed energy systems should fully integrate technical, economic, environmental, and social factors and consider device characteristics, system architecture, and source-load uncertainties. Further, this review presents four modeling perspectives for optimizing and analyzing distributed energy systems, including energy hub, thermodynamics, heat current, and data-driven. The system’s optimal operation and scheduling strategies, disturbance analysis, and related control methods are also discussed from the power system and thermal system, respectively. In all, more research is required for distributed energy systems based on an integrated energy perspective in optimal system structure, hybrid modeling approaches, data-driven system state estimation, cross-system disturbance spread, and multi-subject interaction control.